RELOKASI PKL DAN RESPON KONSUMEN TERHADAP KONDISI SOSIAL EKONOMI PASAR MINI DATAH MANUAH, KOTA PALANGKA RAYA - Grace Hutagalung; Andrie Elia; Elia Elia (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This study aims to examine how the policy of relocating street vendors to Datah Manuah Mini Market affects the social and economic conditions of the market and how consumers view the changes that have taken place. This study uses a descriptive qualitative approach involving five consumer informants through in-depth interviews, observations, and document collection. The results show that the relocation of vendors has had a positive impact on the cleanliness, order, and layout of the market. However, this relocation also caused new problems, such as a decrease in the number of visitors, a less strategic market location, and a lack of facilities such as lighting. Socially, the relationship between vendors and consumers still exists, but the intensity of interaction between the two has decreased dramatically because the market feels emptier. Economically, the vendors' income has decreased significantly, affecting the continuity of their businesses. Consumer perceptions of this relocation policy vary, ranging from supporting the city's development goals to criticizing the accessibility and atmosphere of the market, which did not exist before. These findings indicate that the success of the relocation policy depends on social and economic factors and how consumers understand these changes, as explained in Max Weber's Social Action Theory